Proceedings of Supporting the Social Side of Large-scale Software Development, a CSCW Workshop - Cheng, Li-Te; Cox, Anthony; DeLIne, Robert; Souza, Cleidson de; Schneider, Kevin; Singer, Janice; Storey, Margaret-Anne; Venolia, Gina (Microsoft Research, 2006)
Discusses the importance of scientific explanations in tool design, and various ways of forming such explanations.